Kontroversi Hukuman Cambuk - Ali Abubakar (Media Syari'ah, 2012)
Application of Islamic Shari'a in Aceh introduced flogging as punishment for the perpetrators of violations of Islamic law, gambling, seclusion, and alcohol. Rejection comes from some quarters that assesses punishment cruel and inhumane, and because it violates human rights. Proponents argue that caning is a part of God's law and therefore does not violate human rights. This article contains the philosophical and judicial caning in Aceh, the public perception and its relation to human rights. The result, on the one hand, the attitude of counter flogging occurred because the wrong perception of the Islamic Shari'a. Here another, caning is not of rigid and highly conditional. He is only one alternative punishment that is now considered the most able to achieve the purpose of punishment in Islam.